A piezoelectric nanomaterial and its application

By constructing KNN-AG2O-COO nanomaterials on the surface of the BCP bracket, using ultrasonic stimulation to generate ROS and autoclavere stimulation into osteocytes, solve the problem of insufficient antibacterial and bone induction capabilities in the treatment of BCP brackets in the treatment of infectious bone defects. It has the effect of efficient antibacterial and osteotrophic treatment.

CN118718084BActive Publication Date: 2025-01-28MIANYANG THIRD PEOPLES HOSPITAL

Patent Information

Application Number
CN202410723386.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-01-28
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

Existing BCP stents lack intrinsic osteoinducible and antibacterial properties in the treatment of infectious bone defects, resulting in implant-related infections and failure of bone repair.

Method used

Construct the KNN-AG2O-COO/BCP intelligent response platform, effectively generate ROS damage bacterial membrane through ultrasound stimulation, AG ion release synergistic antibacterial; KNN-AG2O-COO self-polarization stimulates osteocyte proliferation and differentiation, and CO ion release promotes bone bone. And blood vessels.

Benefits of technology

Achieve effectively killing MRSA bacteria under ultrasound stimulation, promoting bone repair and vascular production, and significantly improved the antibacterial performance and bone induction capacity of BCP brackets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118718084B_ABST
    Figure CN118718084B_ABST
Patent Text Reader

Abstract

The invention discloses a piezoelectric nanomaterial and application thereof. A KNN-based nanomaterial is constructed on the surface of a 3D-printed BCP scaffold for treating drug-resistant bacterial biofilm infection: KNN is doped with Ag2O and CoO to construct a phase boundary KNN piezoelectric material to enhance the piezoelectric catalytic activity of KNN; the nano-platform is introduced to the surface of the 3D-printed BCP scaffold, the nano-material efficiently generates ROS under ultrasonic response, quickly destroys MRSA bacterial biofilm at an early stage, and the release of Ag ions synergistically resists bacteria; under the action of pressure, KNN-Ag2O-CoO self-polarization stimulates osteoblast proliferation and differentiation, and the release of Co ions promotes osteogenesis and angiogenesis, further enhancing the later bone repair ability of the material system, thereby realizing a dual synergistic system with both "antibacterial and osteogenesis integration", and solving the insufficient application of BCP scaffolds in infectious bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the application field of piezoelectric nanomaterials, and in particular to a piezoelectric nanomaterial and an application thereof. Background Art

[0002] Infected bone defects are one of the most common and serious complications in orthopedics. They are difficult to repair, take a long time, and have poor results. They are currently the main problem in orthopedics, oral and maxillofacial surgery, and other fields. Implant-associated infections (AIAs) not only aggravate local inflammatory reactions, damage the bone environment, and hinder bone integration, causing local infected bone defects, but also spread bacteria colonized on the surface of the implant to the bone marrow cavity, joint cavity, or enter other organs with the blood, leading to osteomyelitis, bacterial arthritis, and metastatic infection, which seriously endangers the health of patients. Literature reports that the incidence of implant-associated infection in orthopedic surgery is 1-5%, and even as high as 30% in open fractures. The treatment of AIAs usually requires multiple treatment methods, and surgery combined with antibiotic therapy is currently the main clinical intervention. However, during clinical treatment, despite active tissue debridement, various inflammatory mediators and proteolytic enzymes released by residual bacteria still affect bone regeneration. In addition, long-term antibiotic treatment can easily lead to bacterial resistance. According to statistics, more than 40% of resistant Staphylococcus aureus are methicillin-resistant Staphylococcus aureus (MRSA). The colonization of MRSA on the surface of implants has become an urgent problem to be solved. When MRAS infection is not treated promptly and effectively, bacteria adhere to and colonize on the surface of implants to form a biofilm to resist the host's immune attack, inhibit the penetration of bactericides, and further increase the difficulty of antibiotic treatment. At present, most implant optimizations are mainly focused on promoting biocompatibility and bone regeneration through implant surface modification, but ignore the antibacterial properties of implants. Therefore, designing multifunctional implants with good biological activity, antibacterial properties and bone integration ability is the key to preventing implant-related infections and treating infectious bone defects secondary to implant-related infections.

[0003] Biphasic calcium phosphates (BCP) are composed of two calcium-phosphate compounds: hydroxyapatite (HA) and β-tricalcium phosphates (β-TCP). HA is more stable and β-TCP is more soluble, so BCP has better bioactivity and biodegradability than traditional calcium-phosphate compounds [8]. The elemental composition of BCP is similar to that of bone minerals and has been shown to have good biocompatibility and osteoconductivity. However, the use of BCP scaffolds in the treatment of infected bone defects is greatly limited. The main reasons include the following two points: ① Lack of intrinsic bone induction ability: BCP scaffolds lack the ability to induce angiogenesis and osteoblast recruitment and have poor bone induction; ② Insufficient antibacterial properties: When bacteria attach to the scaffold surface, AIAs are prone to occur. The inflammatory infiltration area composed of macrophages and neutrophils secretes a variety of tissue-destructive enzymes to degrade bone matrix, inhibit bone ingrowth at the bone-scaffold interface, induce scaffold loosening, cause bone repair failure, and ultimately lead to infected bone defects. Therefore, designing a scaffold that has both superior anti-infection ability and excellent bone induction ability is an urgent problem that needs to be solved in the current application of BCP in the treatment of infectious bone defect diseases.

[0004] Sonodynamic therapy (SDT) is a new antibacterial treatment method. It is used in the field of bone implant infection research due to its high penetration (>8cm). SDT is a low-intensity ultrasound (0.5-4.0W·cm -2 ) and sonosensitizer activated by sound waves. Under the action of ultrasound, the "cavitation effect" promotes the separation of electron-hole pairs inside the sonosensitizer and combines with H2O and O adsorbed on the surface of the sonosensitizer. 2 Redox reactions occur to produce reactive oxygen species (ROS). ROS can damage bacterial lipids, proteins, DNA helical structures, etc., and can destroy biofilm structures, thereby effectively killing bacteria. Inorganic nanosonosensitizers have shown advantages such as controllable morphology and stable chemical structure. However, traditional inorganic sonosensitizers have low efficiency in producing ROS, which limits their clinical use. Therefore, the development of new inorganic sonosensitizers with excellent biocompatibility and efficient ROS production is the key to SDT antibacterial treatment.

[0005] Potassium sodium niobate [(K,Na)NbO3, KNN] is a piezoelectric material with good biocompatibility. It has piezoelectric catalytic activity under ultrasonic stimulation, which can promote the separation of electron-hole pairs and produce active groups such as hydroxyl radicals (·OH) and superoxide radicals (·O2-). In addition, piezoelectric materials produce electric polarization under the action of mechanical deformation, and accumulate positive and negative charges on the relative surfaces. Its built-in electric field can stimulate the proliferation and differentiation of osteoblasts and contribute to the formation and mineralization of bone matrix. Therefore, SDT combined with KNN piezoelectric materials has good application prospects in the treatment of infected bone defects. However, the piezoelectric catalytic activity of pure KNN materials is relatively poor, the efficiency of ROS generation by ultrasonic responsiveness is low, and the antibacterial ability is limited. It is urgent to study KNN-based piezoelectric materials with high-voltage electrocatalytic activity. In recent years, studies have found that the piezoelectric properties of KNN-based materials have been significantly improved by constructing phase boundary engineering by doping ions or metal oxides, which is also expected to improve their piezoelectric catalytic activity. The preliminary experimental results of the present invention group show that metal oxide doping to construct phase boundary engineering can greatly improve the piezoelectric catalytic activity of KNN-based piezoelectric materials (Research basis 3). Therefore, constructing a composite scaffold modified with phase boundary KNN-based piezoelectric materials to achieve the "antibacterial-osteosynthesis integrated" treatment strategy under SDT is expected to effectively treat infected bone defects.

[0006] In summary, the present invention intends to construct KNN-based nanomaterials on the surface of 3D-printed BCP scaffolds: KNN is doped with Ag2O and CoO to construct phase boundary KNN piezoelectric materials to enhance the piezoelectric catalytic activity of KNN; the nanoplatform is introduced to the surface of the 3D-printed BCP scaffold, and the nanomaterial efficiently produces ROS under ultrasonic response, quickly destroys the bacterial biofilm at an early stage, and the Ag ion release has synergistic antibacterial effect; under the action of pressure, KNN-Ag2O-CoO self-polarization stimulates the proliferation and differentiation of osteoblasts, and the Co ion release promotes osteogenesis and angiogenesis, further enhancing the later bone repair ability of the material system, thereby realizing a dual synergistic system with both "antibacterial and osteogenesis integration", and solving the insufficient application of BCP scaffolds in infectious bone defects. Summary of the invention

[0007] In order to solve the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a piezoelectric nanomaterial and its application. A KNN-Ag2O-CoO / BCP intelligent response platform is constructed, which efficiently produces ROS under ultrasonic stimulation, quickly destroys bacterial biofilm at an early stage, and releases Ag ions for synergistic antibacterial effect; KNN-Ag2O-CoO self-polarization stimulates osteoblast proliferation and differentiation, and Co ion release promotes osteogenesis and angiogenesis, further improving the late bone repair ability of BCP scaffolds, thereby realizing a dual synergistic system with both "antibacterial and osteogenesis integration", solving the insufficient application of BCP scaffolds in infectious bone defects.

[0008] To achieve the above object, the technical solution of the present invention is:

[0009] A piezoelectric nanomaterial KNN-Ag2O-CoO,

[0010] The specific operation of preparing the nanomaterial is as follows: K0.48Na0.52NbO3-0.2%molAg2O-0.2%molCoO (hereinafter referred to as KNN-Ag2O-CoO) piezoelectric nanomaterial is synthesized by traditional solid phase sintering method, and stoichiometric proportions of K2CO3, Na2CO3, Nb2O5, Ag2O and CoO are added to a nylon bottle, and then an appropriate amount of alcohol and 1mm diameter zirconia balls (the volume ratio of each component is: powder material: anhydrous ethanol: zirconia balls = 1:1:1-3) are added to the nylon bottle, mixed with alcohol and zirconia balls in the nylon bottle and fully mixed, and then ball milled in a ball mill (120RPM) for 24 hours, and then the dried powder is calcined at 850°C for 6h to obtain the piezoelectric nanomaterial KNN-Ag2O-CoO.

[0011] The physical and chemical properties of the material are as follows: KNN-Ag2O-CoO presents a hexahedral structure, and the mapping diagram shows that the elements Na, K, Nb, Ag, and Co are evenly distributed inside the nanomaterial; XRD results show that the 2θ angle is at 45-46, and due to the doping of metal oxides, the crystal phase structure of the nanomaterial changes and the characteristic peak shifts; UV diffuse reflectance results show that the bandgap width (E g ) is 3.28 eV, and KNN’s E g After doping with metal oxides, the bandgap width of the nanomaterials is reduced, which is more conducive to the production of ROS by ultrasound activation; the XPS valence band (E VB ) The analysis results show that the E of KNN-Ag2O-CoO VB is 2.58eV, KNN's E VB is 2.35eV; according to E CB =E VB -E g , the conduction band of KNN-Ag2O-CoO (E CB ) is -0.7eV; E VB is enough to reach the OH / H2O oxidation potential (+1.99 eV), while E CB (-0.7eV) is sufficient to promote O2 / ·02 - Oxygen reduction reaction (-0.33 eV), therefore, according to theoretical calculations, it can effectively produce ROS under ultrasound stimulation.

[0012] Furthermore, a 3D printed BCP scaffold loaded with piezoelectric nanomaterials based on piezoelectric nanomaterials KNN-Ag2O-CoO is obtained by the following steps:

[0013] The 3D printed BCP scaffold was added to 30ml acetone-30ml ultrapure water-30ml ethanol-30ml ultrapure water solution in sequence, and ultrasonically cleaned for 10min each time; the cleaned 3D printed BCP scaffold was placed in a 50ml beaker and immersed in a container containing 20ml Tris-HCl solution (PH = 8.5) added to the beaker (scaffold volume: solution volume = 1:3), and then an appropriate amount of dopamine powder (concentration of 3mg / ml) was weighed according to the volume of the solution and added to the beaker 60mg DA, stirred for 24h (300RPM) under light-proof conditions to obtain a BCP@PDA scaffold with polydopamine attached; BCP@PDA was taken out, and the scaffold was cleaned with an appropriate amount of ultrapure water under ultrasound to remove unattached impurities; 4mg KNN-Ag2O-CoO powder that had been fully dissolved in advance was weighed and added to 20ml ultrapure water solution (200ug / ml), and ultrasonically shaken to fully disperse; the BCP@PDA scaffold was added to the KNN-Ag2O-CoO solution, and shaken for 12h (120RPM) under light-proof conditions, the scaffold loaded with nanomaterials was taken out, and the scaffold was cleaned three times with an appropriate amount of ultrapure water to remove unattached drugs, and after drying, the KNN-Ag2O-CoO / BCP scaffold, that is, the 3D printed BCP scaffold loaded with piezoelectric nanomaterials system, was obtained.

[0014] The application of the piezoelectric catalytic nanomaterial in 3D printing of BCP scaffolds is to construct KNN-based nanomaterials on the surface of the 3D printed BCP scaffolds for treating drug-resistant bacterial biofilm infections: KNN is doped with Ag2O and CoO to construct phase-boundary KNN piezoelectric materials to enhance the piezoelectric catalytic activity of KNN; the nanoplatform is introduced to the surface of the 3D printed BCP scaffolds, the nanomaterials efficiently generate ROS under ultrasonic response, quickly destroy MRSA bacterial biofilms at an early stage, and the release of Ag ions synergistically resists bacteria; under the action of pressure, KNN-Ag2O-CoO self-polarization stimulates osteoblast proliferation and differentiation, and the release of Co ions promotes osteogenesis and angiogenesis, further enhancing the later bone repair ability of the material system.

[0015] Compared with the prior art, the beneficial effects of the present invention are:

[0016] Compared with the traditional BCP scaffold, the KNN-Ag2O-CoO / BCP scaffold has excellent antibacterial properties, effectively killing MRSA bacteria and removing bacterial biofilm under ultrasound stimulation. The in vitro antibacterial results show that it can effectively kill 98.61% of MRSA under ultrasound. In addition, based on its piezoelectric activity, the proliferation and differentiation ability of osteoblasts is enhanced, and the release of Co elements promotes the enhancement of angiogenesis, further enhancing the osteogenic ability of KNN-Ag2O-CoO / BCP. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 .KNN-based nanomaterials and their characterization;

[0018] Figure 1 A: SEM of different KNN-based nanomaterials; Figure 1 B. Figure 1 C: TEM image and mapping image of KNN-Ag2O-CoO; Figure 1 D: XRD results of different materials; Figure 1 E: Differences in XRD characteristic peaks of different materials; Figure 1 F: UV-VIS analysis results; Figure 1 G: XPS valence band analysis results.

[0019] Figure 2 .SEM and mapping images of drug-loaded stent;

[0020] Figure 3 .KNN-Ag2O-CoO has ultrasound-responsive high-voltage electrocatalytic activity;

[0021] Figure 3 A: Ultrasonic response degradation of MB and detection of ·OH by KNN-Ag2O-CoO nanomaterials; Figure 3 B: Ultrasonic response of KNN-Ag2O-CoO nanomaterials to degrade DPBF and detect ·O2-; Figure 3 C: SOSG fluorescence detection of 1O2 produced by different concentrations of KNN-Ag2O-CoO in response to ultrasound; Figure 3 D: SOSG fluorescence detection of 1O2 produced by different KNN-based nanomaterials in response to ultrasound; Figure 3 E. Figure 3 F: ESR detection of 1O2 and ·O2- produced by ultrasonic response of KNN-Ag2O-CoO.

[0022] Figure 4 .KNN-Ag2O-CoO has excellent antibacterial properties;

[0023] Figure 4 A: Antibacterial coating effects of different composite stent systems under non-ultrasound and ultrasonic stimulation; Figure 4 B: SEM observation shows that the surface biofilm structure of KNN-Ag2O-CoO / BCP was completely destroyed after ultrasonic stimulation, as shown by the red arrow;

[0024] Figure 5 .TEM images of MRSA morphological changes under non-ultrasound and ultrasound of KNN-Ag2O-CoO;

[0025] Figure 6 .CKK-8 detection in co-culture of scaffold and cells;

[0026] Figure 7 .ALP and ARS staining

[0027] Figure 8 . Steps for establishing an animal model of implant infection;

[0028] Fig. 9 .HE and Giemsa staining of femoral condyle one week after modeling;

[0029] In the figure, the yellow five-pointed star indicates the location of the stent, the blue arrow indicates inflammatory cells, and the red arrow indicates MRSA.

[0030] Fig.10 .Muscle HE and Giemsa staining images;

[0031] In the figure, blue arrows: inflammatory cells; red arrows: MRSA.

[0032] Fig.11 .Osteogenesis images at 4 and 8 weeks;

[0033] In the figure, green represents new bone and white represents scaffold. DETAILED DESCRIPTION

[0034] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments:

[0035] like Figure 1-11 As shown,

[0036] (1) Successfully prepared KNN-Ag2O-Co piezoelectric material

[0037] The piezoelectric catalytic nanomaterial K0.48Na0.52NbO3-0.2%molAg2O-0.2%molCoO (abbreviated as KNN-Ag2O-CoO) was synthesized by conventional solid phase sintering method. The stoichiometric ratio of K2CO3, Na2CO3, Nb2O5, Ag2O and CoO was added to a nylon bottle, and then an appropriate amount of alcohol and 1mm diameter zirconia balls (the volume ratio of each component was: powder material: anhydrous ethanol: zirconia balls = 1:1:1) were added to the nylon bottle, mixed with alcohol and zirconia balls in the nylon bottle, and then milled in a ball mill at a speed of 120RPM for 24 hours, and then the dried powder was calcined at 850℃ for 6h to obtain the piezoelectric nanomaterial KNN-Ag2O-CoO. Take appropriate amount of KNN, KNN-Ag2O, KNN-CoO, KNN-Ag2O-CoO nanomaterials and add them to anhydrous ethanol solution, respectively configured to 100ug / mL, take appropriate amount of each solution and spin-coat it on the titanium sheet, and dry it at room temperature for 30min; fix the bracket with each nanomaterial spin-coated on the sample stage and spray gold for 60s, and take out the sample for inspection and observation. The SEM parameters are working voltage 40KV, acceleration current 30mA; TEM can observe the microscopic morphology and structure inside the material, reduce the error of material morphology caused by material accumulation and overlap, take an appropriate amount of nanomaterials and dissolve them in anhydrous ethanol to a concentration of 20ug / ml, fully disperse them with an ultrasonic oscillator, and use a pipette to draw 10uL of the dispersed sample suspension and drop it on the copper mesh. After the ethanol is naturally air-dried and evaporated, scan the copper mesh again, use an EDS spectrometer to scan and analyze the distribution of elements on the surface of the material, and draw the distribution maps of the six elements Na, K, O, Nb, Ag, and Co respectively; take 100mg of each synthesized powder nanomaterial for X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) detection. The SEM results show that the KNN-Ag2O-CoO nanomaterial is hexahedral with a particle size of about 500nm ( Figure 1 A), TEM further confirmed that the synthesized KNN-Ag2O-CoO has a hexahedral structure, and the mapping diagram shows that the elements Na, K, Nb, Ag, O, and Co are evenly distributed inside the nanomaterial ( Figure 1 C). XRD results show that at 2θ angle of 45-46, due to the doping of metal oxides, the crystal phase structure of the nanomaterial changes and the characteristic peak shifts ( Figure 1 E). The UV diffuse reflectance results show the bandgap width of KNN-Ag2O-CoO (E g ) is 3.28 eV, and KNN’s E g is 3.34eV( Figure 1 F). After doping with metal oxides, the bandgap width of the nanomaterials is reduced, making it more conducive to being activated by ultrasound to produce ROS. XPS valence band (E VB) The analysis results show that the E of KNN-Ag2O-CoO VB is 2.58eV, KNN's E VB 2.35eV( Figure 1 G) According to E CB =E VB -E g , the conduction band of KNN-Ag2O-CoO (E CB ) is -0.7eV. VB is enough to reach the OH / H2O oxidation potential (+1.99 eV), while E CB (-0.7eV) is sufficient to promote O2 / ·02 - Oxygen reduction reaction (-0.33 eV), therefore, according to theoretical calculations, it can effectively produce ROS under ultrasound stimulation.

[0038] (2) Successfully constructed 3D printed KNN-Ag2O-CoO / BCP composite scaffold

[0039] The 3D printed BCP scaffold was added to the order of 30ml acetone-30ml ultrapure water-30ml ethanol-30ml ultrapure water solution and ultrasonically cleaned for 10min each time; the cleaned 3D printed BCP scaffold was placed in a 50ml beaker and immersed in a container containing 20ml Tris-HCl solution (PH = 8.5) added to the beaker (scaffold volume: solution volume = 1:3), and then an appropriate amount of dopamine powder (concentration of 3mg / ml) was weighed according to the volume of the solution and added to the beaker 60mg DA, stirred for 24h (300RPM) under light-proof conditions to obtain BCP@PDA scaffolds with polydopamine attached; BCP@PDA was taken out, and the scaffolds were cleaned under ultrasound with an appropriate amount of ultrapure water to remove unattached impurities; 4mg of KNN-Ag2O-CoO powder that had been fully dissolved in advance was weighed and added to 20ml of ultrapure water solution (200ug / ml), and ultrasonically shaken to fully disperse; the BCP@PDA scaffold was added to the KNN-Ag2O-CoO solution, and the mixture was shaken on a shaker under light-proof conditions. After 12 hours of treatment (120RPM), the nanomaterial-loaded stent was taken out, and the stent was washed three times with appropriate amount of ultrapure water to remove the unattached drugs. After drying, the KNN-Ag2O-CoO / BCP stent was obtained; the obtained stent was fixed on the sample stage with conductive glue and sprayed with gold for 60 seconds for SEM observation. The SEM parameters were working voltage 40KV and acceleration current 30mA; the surface of the stent was scanned by EDS spectrometer to analyze the surface element composition, and the distribution maps of six elements, Na, K, O, Nb, Ag, and Co, were drawn respectively. The results are shown in Figure 2As shown: after polydopamine adheres, the 3D printed BCP scaffold changes from white to black; SEM observation of the scaffold surface shows that calcium-phosphorus compounds are accumulated in granular form to form a 3D printed structure, and the void structure inside the scaffold is conducive to the flow of cell nutrient solution; small polydopamine particles are evenly distributed on the surface of each scaffold, and hexagonal KNN-based nanomaterials can be observed to be successfully loaded on the scaffold surface; Mapping results show that Na, K, Nb, O, Ag, and Co elements are evenly distributed on the scaffold surface. (3) KNN-Ag2O-CoO has ultrasonic response high-voltage electrocatalytic activity

[0040] 1,3-Diphenylisobenzofuran (DPBF) is a 1 O2 and O 2- The capture agent can be effectively 1 O2 and O 2- Degradation is often used to detect the ultrasonic response ability of acoustically sensitive materials. 10 μL DPBF solution (10 mg / mL) was added to 2 ml (100 ug / mL) KNN-Ag2O-CoO ethanol solution and placed in a dark environment for 0.5 h. Then ultrasonically ultrasonicated for 12 min (1 MHz, 50% duty cycle, 1.5 W cm -2 ), the supernatant of the samples was collected every 3 minutes, and the changes in the absorption intensity of each material group at 420 nm were detected by UV-visible absorption spectroscopy to detect the ability of different materials to produce singlet oxygen.

[0041] Singlet oxygen sensor green reagent (SOSG) 1 O2 is highly selective 1 O2 emits green fluorescence after binding, often used in solution systems 1 Detection of O2. Take an appropriate amount of SOSG and dissolve it in DMSO solution to prepare a 5mM working solution; take 1uL of SOSG solution and add it to 2mL of KNN-Ag2O-CoO aqueous solution with different concentrations (5, 50, 100, 200μg / ml), mix well, and ultrasonicate for 12min (1MHz, 50% duty cycle, 1.5W cm -2 ), the supernatant of the sample was collected, and the fluorescence intensity change at 525nm was detected by a fluorescence detector to compare the fluorescence intensity of different concentrations of nanomaterials. 1 O2 difference.

[0042] Methylene blue (MB) is often used as a capture agent to verify the conversion of 10 μg mL -1The methylene blue aqueous solution was added with 2 ml (100 μg / mL) of KNN-Ag2O-CoO aqueous solution, and the mixture was incubated at 37 °C for 1 h. The mixture was ultrasonicated for 12 min (1 MHz, 50% duty cycle, 1.5 W cm -2 ), UV-visible absorption spectroscopy was used to detect the change in the absorption intensity of the solution at 665 nm to detect the ability of the nanomaterial to produce ·OH under ultrasound. 100 μg / ml KNN-Ag2O-CoO solution was placed in a test tube and ultrasonicated for 10 min in a dark room (1 MHz, 50% duty cycle, 1.5 W cm -2 ), take the upper liquid and detect it with ESR spectrometer 1 O2 and O 2- The ESR detection parameters are as follows: central magnetic field: 3505.00G; frequency: 9.843138GHz; power: 12.62mW; power attenuation 12.0dB.

[0043] The results are as follows Figure 3 As shown: KNN-Ag2O-CoO nanomaterials can produce ·OH in response to ultrasound. The produced ·OH reacts with MB, resulting in a decrease in its absorbance at 665nm, as shown in Figure 3 As shown in A, at 0 min, the absorbance of the material and MB mixture at 665 nm was 1.41. With the extension of ultrasonic time, the generated ·OH gradually increased. After 12 min of ultrasonic treatment, the absorbance at 665 nm dropped to 0.80. In addition, the ultrasonic response of KNN-Ag2O-CoO nanomaterials can produce ·O2 - , and also has time dependence, that is, as the ultrasound time increases, the generated ·O2 - At 0 min, the absorbance of the mixed solution of KNN-Ag2O-CoO and DPBF at 420 nm was 1.26. With the extension of ultrasonic time, the generated ·O 2- The absorbance at 420 nm decreased to 0.84 after 12 min of ultrasound. In addition, the KNN-Ag2O-CoO nanomaterials produced 1 O2, and has concentration dependence, that is, as the material concentration increases, the fluorescence intensity of the material and SOSG mixture at 525nm increases, representing the generated 1 Increased O2 Figure 3 C); Compared with KNN, KNN-Ag2O and KNN-CoO, KNN-Ag2O-CoO has the strongest ultrasonic response piezoelectric catalytic performance, such as Figure 3As shown in Figure 4, after the mixed solution of each material and SOSG was ultrasonicated for 12 minutes under the same conditions, the fluorescence intensity of KNN at 525nm was 764.69, KNN-Ag2O was 11330.29, KNN-CoO was 1338.29, and KNN-Ag2O-CoO was 3243.83; ESR further verified that KNN-Ag2O-CoO could produce different ROS under ultrasonic stimulation, and the ROS produced increased with the increase of ultrasonic time ( Figure 3 E, 3F).

[0044] (4) KNN-Ag2O-CoO has excellent antibacterial properties

[0045] Take a 24-well plate, add KNN / BCP, KNN-Ag2O / BCP and KNN-CoO / BCP, KNN-Ag2O-CoO / BCP scaffold, and UV irradiate for 30 minutes before use. Take 2 mL of diluted methicillin-resistant Staphylococcus aureus (MRSA) solution (10 5 CFU / mL) were added to each well plate. The non-ultrasound group was co-cultured at room temperature for 30 min, and the ultrasound group was placed on an ultrasound machine for 12 min (1 MHz, 50% duty cycle, 1.5 W cm -2 ). Then take 50 μL of bacterial liquid from the well plate and drop it onto the solid culture medium, and spread it with sterilized glass beads. Make three parallel samples for each group. Finally, put the culture dish into a 37℃ incubator and incubate for 12 hours. When the bacteria grow to a suitable colony size, take pictures and record them, and count the number of bacterial colonies in each group.

[0046] Place the KNN-Ag2O-CoO / BCP scaffold into a 24-well plate and add 2 mL of diluted MRSA solution (10 6 CFU / mL) for 5 days, and the bacterial culture medium was replaced every 24 hours; the stents in the ultrasound group were placed on an ultrasound machine and ultrasound was performed for 12 min (1 MHz, 50% duty cycle, 1.5 W cm -2 ); the non-ultrasound group was not treated. Then the stents in the well plate were taken out and fixed with 4% formaldehyde solution for 2 hours, dehydrated with ethanol solution gradient (30%-50%-70%-90%-95%-100%), and the treated stents were placed at room temperature to dry naturally; the prepared stents were fixed on the stage with conductive glue and sprayed with gold for 60 seconds before SEM observation. The SEM parameters were working voltage 40KV and accelerating current 30mA.

[0047] Antibacterial plate counting was performed on each group. The results showed that in the non-ultrasonic state, the bacterial count of the blank control group was 720±56, which was not statistically different from the KNN / BCP (712±10), KNN-Ag2O / BCP (668±20), KNN-CoO / BCP (701±10) and KNN-Ag2O-CoO / BCP (682±13) groups. After ultrasonic treatment, the bacterial count of the KNN-Ag2O-CoO / BCP group was the least ( Figure 4 A), 10 ± 3, showing the best antibacterial effect, significantly lower than the blank control group (658 ± 20) KNN / BCP (546 ± 9), KNN-Ag2O / BCP (354 ± 15), KNN-CoO / BCP (322 ± 16) ( Figure 4 C), that is, KNN-Ag2O-CoO / BCP can effectively kill 98.61% of MRSA under ultrasound; the KNN-Ag2O-CoO / BCP group and MRSA were co-cultured in a 37°C constant temperature incubator for 5 days to form a bacterial biofilm, and the scaffold system was subjected to ultrasound. SEM observations showed that the biofilm structure was completely destroyed after ultrasound treatment ( Figure 4 B). TEM results show ( Figure 5 ): In the non-ultrasonic state, KNN-Ag2O-CoO does not affect the morphological structure of bacteria; after ultrasonic stimulation, the morphological structure of bacteria is destroyed, the bacterial membrane ruptures (red arrows), and the cytoplasm shrinks (green star).

[0048] (5) (5) KNN-Ag2O-CoO / BCP scaffold has good tissue compatibility

[0049] The cell safety of BCP@PDA, KNN / BCP, KNN-Ag2O / BCP, KNN-CoO / BCP and KNN-Ag2O-CoO / BCP was determined by CCK-8 method: ① The scaffold was sterilized with high temperature and high pressure steam ② The P3 generation MC3T3 cells were rinsed with PBS and then digested with trypsin. The digestion was terminated by the culture medium and the cells were counted under a microscope using a cell counting plate; ③ MC3T3 cells were added to a 24-well plate at a density of 20,000 cells / well, and each drug-loaded scaffold system was added. After the operation, the well plate was placed in a cell incubator for culture and the temperature was adjusted to 37°C. The medium was changed every two days; ④ A 10% volume fraction CCK-8 working solution (stock solution: culture medium = 1:9) was prepared. On the 1st, 3rd and 5th days of culture, the well plate culture medium was removed, 100 μL CCK-8 working solution was added, and incubated for 2 hours before detection; the absorbance value of each well at a wavelength of 450 mm was recorded.

[0050] The results are as follows Figure 6As shown in the figure: there was no significant difference in the OD values ​​of each group of scaffolds measured on the 1st, 3rd and 5th days, which proved that each group of scaffolds had good biocompatibility; in addition, we found that the OD value of the KNN-Ag2O-CoO / BCP group was significantly reduced compared with other scaffold groups on the 1st and 3rd days under US treatment. When MC3T3-E1 cells were cultured to the 5th day, the cell viability of KNN-Ag2O-CoO / BCP recovered to the same level as other scaffold groups.

[0051] (6) KNN-Ag2O-CoO / BCP has excellent osteogenic ability

[0052] BCP@PDA, KNN / BCP, KNN-Ag2O / BCP, KNN-CoO / BCP, and KNN-Ag2O-CoO / BCP were placed in a 24-well plate, and MC3T3-E1 cells at a concentration of 20,000 cells / mL were added to the scaffolds. The scaffolds were placed in a constant temperature incubator at 37°C for culture, and the culture medium was replaced every 24 hours. When the cell fusion reached 70%, the complete culture medium in the well was removed and replaced with osteoinduction culture medium, and the cells were incubated in a constant temperature incubator, and the osteoinduction culture medium was replaced every 48 hours. On the 14th and 21st days, respectively, the scaffolds were cultured in a constant temperature incubator. After d, the scaffolds to be measured were taken out, the osteogenic induction medium was removed, the scaffolds were gently rinsed with PBS, and then formaldehyde was fixed for 2h. 300ul of Alizarin Red S dye was added to each well for staining for 10min. At the same time, the scaffolds to be measured were taken out after 7d and 14d, the osteogenic induction medium was removed, the scaffolds were gently rinsed with PBS, and then formaldehyde was fixed for 2h. The prepared working solution was added to each well and incubated at room temperature in the dark for 30min. The ARS and ALP dyes were removed, and PBS was used as the washing solution for washing twice, each time for 5min. After washing, the scaffolds were observed under a microscope and pictures were collected. Three parallel groups were set up for each group. The results are shown in Figure 2. Figure 7 As shown: On the 7th day of osteoinduction, KNN / BCP, KNN-Ag2O / BCP and KNN-CoO / BCP, KNN-Ag2O-CoO / BCP groups had obvious ALP deposition, and the deposition in KNN-Ag2O-CoO / BCP group was more obvious, and ALP staining was deeper; on the 14th day, the staining in each group was more obvious than that on the 7th day, while the ALP deposition in the blank group was not obvious ( Figure 7 B); Image J semi-quantitative results showed that the KNN-Ag2O-CoO / BCP group was significantly larger than the other groups on days 7 and 14 (P<0.05) ( Figure 7 C); For ARS staining, on the 14th day, the KNN / BCP, KNN-Ag2O / BCP and KNN-CoO / BCP groups had obvious red calcium crystal deposition, while the ARS deposition in the blank group was not obvious; on the 21st day, the red calcium crystal deposition of each scaffold further increased ( Figure 7 A); Image J semi-quantitative results showed that the calcium salt crystals in the KNN-Ag2O-CoO / BCP group were significantly larger than those in the other groups on days 14 and 21, and the difference was statistically significant (P < 0.05) ( Figure 7 D).

[0053] (7) The research team is proficient in modeling implant infection animal models

[0054] The four sets of scaffolds (φ3mm X 4mm) prepared in advance, namely BCP@PDA, KNN / BCP, KNN-Ag2O / BCP, KNN-CoO / BCP, and KNN-Ag2O-CoO / BCP, were sterilized by ultraviolet irradiation for 12h in a clean bench. Then, each scaffold was placed in a 24-well plate, and 1ml of MRSA bacterial solution (concentration of 10 6 CFU / mL), put the well plate into a 37℃ constant temperature shaker for 24 hours before use; use a small animal gas anesthesia machine to induce anesthesia. After the SD rat is anesthetized successfully, prepare the skin of the surgical area, fix the rat in a lateral position on the experimental table, and disinfect the surgical area 3 times with Eric; after touching the position of the femoral condyle with the hand, make a 1cm long transverse incision to expose the lateral femoral condyle and femoral pulley; the drill with a 3mm drill bit enters vertically from the center of the lateral femoral condyle, and the drilling depth is about 4mm; use gauze to stop bleeding at the drilling site, implant the prepared bacterial scaffold into the bone defect, and fill the bone defect with bone wax; rinse the surgical wound with saline, suture the muscle and skin incisions in turn, and disinfect with Eric; wait for it to wake up naturally to observe whether it can walk, and transfer it to the breeding room if there is no abnormality. Observe the rats' eating, mental activity, and wound healing every day ( Figure 8 ).

[0055] (8) Animal model results show that KNN-Ag2O-CoO / BCP has excellent antibacterial properties

[0056] Femurs of SD rats were obtained and fixed with 4% paraformaldehyde for 2 weeks. After fixation, the femurs were decalcified with decalcification solution for 4 weeks. HE and Giemsa staining were performed to observe the inflammation level and local bacterial infection of tissues around the stent. The experimental results showed that compared with other groups, the KNN-Ag2O-CoO / BCP group had the mildest local inflammatory reaction (the blue arrows indicate inflammatory cells) and the least bacteria in the surrounding tissues (the red arrows indicate bacteria, which are stained purple-red) ( Fig. 9 A); Image J semi-quantitative results showed that the neutrophil content in the femoral tissue of KNN-Ag2O-CoO / BCP group ( Fig. 9 B) Bacterial content ( Fig. 9C) was significantly lower than that of the other groups, and the difference was statistically significant (P < 0.05); similarly, the staining results of the muscle tissue around the modeling mouth also showed that the KNN-Ag2O-CoO / BCP group had the mildest local inflammation and the least bacteria ( Fig.10 A); Image J semi-quantitative results showed that the neutrophil content in muscle tissue of KNN-Ag2O-CoO / BCP group ( Fig.10 B) and bacterial content ( Fig.10 C) was significantly lower than that of other groups, and the difference was statistically significant (P<0.05) ( Fig.10 )”).

[0057] 10 Analysis of new bone tissue

[0058] At 4 and 8 weeks after surgery, the femoral condyles of SD rats (including the scaffold) were obtained for Micro CT scanning and analyzed using Imaris software. The results are shown in Fig.11 As shown in the figure (green represents new bone tissue, white represents implanted scaffold), from top to bottom, they represent the three-dimensional reconstruction overall image, scaffold and osteogenic integration image, osteogenic side view and osteogenic top view, respectively. The new bone tissue in the scaffold of the six groups at the 8th week was significantly more than that at the 4th week; in addition, the KNN-Ag2O-CoO / BCP group had significantly more new bone tissue than the other groups at the 4th and 8th weeks, and it was observed that the bone tissue around the scaffold was less dissolved and the bone tissue destruction was lighter; further, we quantitatively analyzed the osteogenesis in the femoral condyle scaffold after Micro CT scanning, and analyzed the bone tissue volume of the new bone (BV / TV). The calcium salt crystals in the KNN-Ag2O-CoO / BCP group were significantly larger than those in the other groups, and the difference was statistically significant, indicating that the KNN-Ag2O-CoO / BCP group had the most new bone tissue at the 4th and 8th weeks.

[0059] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that are not conceived through creative work should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined in the claims.

Claims

1. A piezoelectric catalytic nanomaterial, characterized in that: The material is KNN-Ag2O-CoO: The physical and chemical properties of the material are as follows: KNN-Ag2O-CoO has a hexahedral structure, and the mapping diagram shows that the elements Na, K, Nb, Ag, and Co are evenly distributed inside the nanomaterial; XRD results show that 2 θ At angle 45-46, due to the doping of metal oxides, the crystal phase structure of the nanomaterial changes and the characteristic peak shifts; the UV diffuse reflectance results show that the bandgap width E of KNN-Ag2O-CoO g is 3.28 eV, and KNN’s E g is 3.34 eV; after doping with metal oxides, the bandgap width of the nanomaterials is reduced, which is more conducive to being activated by ultrasound to produce ROS; the XPS valence band E VB The analysis results show that the E of KNN-Ag2O-CoO VB is 2.58 eV, KNN’s E VB is 2.35 eV; according to E CB =E VB -E g , the conduction band E of KNN-Ag2O-CoO is calculated CB is -0.7 eV; E of KNN-Ag2O-CoO VB is enough to reach the oxidation potential of ·OH / H2O +1.99 eV, while E CB is -0.7 eV, which is enough to promote O2 / ·02 - The oxygen reduction reaction requires -0.33 eV, so according to theoretical calculations, it can effectively generate ROS under ultrasound stimulation; The preparation method of the nano material is as follows: K is synthesized by solid phase sintering method. 0.48 Na 0.52 NbO3-0.2%molAg2O-0.2%molCoO piezoelectric nanomaterials, add stoichiometric proportions of K2CO3, Na2CO3, Nb2O5, Ag2O and CoO into a nylon bottle, then add appropriate amount of alcohol and 1mm diameter zirconia balls into the nylon bottle, mix thoroughly, then ball mill at 120RPM for 24 hours in a ball mill, then calcine the dried powder at 850℃ for 6h to obtain the piezoelectric nanomaterial KNN-Ag2O-CoO.

2. The piezoelectric catalytic nanomaterial according to claim 1, characterized in that: The volume ratio of each component in the preparation method is: Powder material: Alcohol: zirconium oxide ball = 1:1:1-3.

3. A 3D printed BCP scaffold based on the piezoelectric catalytic nanomaterial of claim 1 or 2; obtained by the following steps: The 3D printed BCP scaffold was added to 30 ml acetone-30 ml ultrapure water-30 ml ethanol-30 ml ultrapure water solution in sequence, and ultrasonic cleaning was performed for 10 min each time. The cleaned 3D printed BCP scaffold was placed in a 50 ml beaker, and an appropriate amount of Tris-HCl solution PH=8.5 was added to the beaker, and the scaffold volume: solution volume = 1:

3. Then, according to the volume of the solution, an appropriate amount of dopamine powder with a concentration of 3 mg / ml was weighed and added to the beaker, and stirred at 300 RPM for 24 h under light-proof conditions to obtain a BCP@PDA scaffold with polydopamine attached. The BCP@PDA was taken out, and the scaffold was cleaned under ultrasonic cleaning with an appropriate amount of ultrapure water to remove unattached impurities. 4 mg of KNN-Ag2O-CoO powder was weighed and added to 20 ml, 200 ug / ml ultrapure water solution, and fully disperse it by ultrasonic vibration; take the BCP@PDA scaffold and add it to the KNN-Ag2O-CoO solution, and treat it on a shaker at 120RPM for 12 hours under light-proof conditions, take out the scaffold loaded with nanomaterials, wash the scaffold three times with appropriate amount of ultrapure water to remove the unattached drugs, and obtain the KNN-Ag2O-CoO / BCP scaffold after drying.

Citation Information

Patent Citations

  • Lead-free piezoceramic-polyvinyl alcohol (PVA) piezoelectric composite material and preparation method thereof

    CN101661991A

  • Piezoelectric driving element, multilayer lead-free piezoelectric ceramic and preparation method of piezoelectric ceramic

    CN104529445A

Cited By

  • Preparation method and application of ruthenium-doped VBS piezoelectric hydrogel

    CN121775219A